Functional evolution equations with nonconvex lower semicontinuous multivalued perturbations - A. G. Ibrahim (International Journal of Mathematics and Mathematical Sciences)
In this paper we prove some existence theorems concerning the solutions and integral solution for functional (delay) evolution equations with nonconvex lower semicontinuous multivalued perturbations.